The benefits of item-method-directed forgetting. - Goernert, Phillip N.; Corenblum, Barry (Memory, 2024)
The present experiments examined the encoding and retrieval conditions in an item-method-directed forget (IMDF) study that included a novel control condition. In the IMDF condition, half of the items were followed by a remember cue whereas the other half were followed by a forget cue. In a remember-both control condition, half of the items were followed by an item identifier called Set A; whereas the other half of the items were followed by a Set B identifier. At the test, items were recalled as a function of the instruction cue or the set identifier. Across two experiments, directed-forgetting effects and associated benefits were found. Further, results from both studies revealed a new way to demonstrate the benefit of IMDF – directed-forgetting participants made more correct source attributions compared to remember-both participants. These benefits were obtained using a within-subjects IMDF paradigm (Experiment 1) as well as a between-subjects IMDF paradigm (Experiment 2). These patterns of results are consistent with several current theories of item-method-directed forgetting.